Resonant recoveries : French music and trauma between the world wars - Rogers, Jillian C. (2021)
'Resonant Recoveries' illustrates that coping with trauma was a central concern for French musicians active after World War I. The losses and violent warfare of World War I shaped how interwar French musicians - from those fighting in the trenches and working in military hospitals to more well-known musicians - engaged with music. Situated at the intersections of musicology, history, sound and performance studies, and psychology and trauma studies, this book argues that modernists' compositions and musical activities were sonorous locations for managing and performing trauma.